The performance of the EQ-5D-Y-5L compared to the EQ-5D-Y-3L in children and adolescents with cerebral palsy (CP) - Janine Verstraete; Des Scott (Elsevier, 2022)
Objectives: The aim of this study is to compare the performance and validity of the EQ-5D-Y-3L (Y-3L) and EQ-5D-Y-5L (Y-5L) in South African children and adolescents with cerebral palsy (CP). Methods: Children/adolescents with CP and those from the general population completed the Y-5L, Y-3L, and PedsQL. Physiotherapists at the school classified participants' functional ability on the Gross Motor Functioning Classification System (GMFCS). Results: Fifty-one children/adolescents completed the measures. The ceiling effect had a 44% relative reduction for Mobility and floor effects decreased across all dimensions except for Looking After Myself when moving from the Y-3L to Y-5L. Informativity of dimensions improved on average by 0.27 on the Y-5L with similar evenness. There was a range of 6-16% inconsistent responses when moving from the Y-3L to the Y-5L. Convergent validity was strong on paired Y-3L and Y-5L dimensions: Kendall's Tau B (range 0.53 - 0.85) and Gamma (range 0.79 - 0.99). There was significant moderate association between Y-3L and Y-5L with similar items on the PedsQL. The physical dimensions of Mobility, Looking After Myself and Usual Activities were significantly associated with GMFCS with those having less independent mobility reporting more severe problems on dimension scores. Conclusion: The Y-5L showed a notable reduction in ceiling and floor effects, improved discriminatory power, higher criterion validity with the GMFCS and similar concurrent validity with the PedsQL as the Y-3L. It is recommended that the Y-5L is further tested for reliability and responsiveness in this population group so that its utility for detecting change in clinical trials or as a routine outcome measure can be determined.